Constrained geometry scandium permethylindenyl complexes for the ring-opening polymerisation of l- and rac-lactide. - Diteepeng, N; Buffet, J; Turner, Z; O'Hare, D (Royal Society of Chemistry, 2019)
The synthesis and characterisation of constrained geometry scandium permethylindenyl chloride, aryloxide and borohydride complexes Me2SB(tBuN,I*)Sc(Cl)(THF) (1), Me2SB(tBuN,I*)Sc(O-2,6-iPr-C6H3)(THF) (2), Me2SB(tBuN,I*)Sc(O-2,4-tBu-C6H3)(THF) (3) and Me2SB(tBuN,I*)Sc(BH4)(THF) (4) are reported. The activity of complexes 1-4 as initiators for the ring-opening polymerisation (ROP) of l- and rac-lactide is presented. The ROP of l- and rac-lactide using complexes 2 and 3 show first-order dependence on monomer concentration, and produced isotactic polylactide (PLA) and moderately heterotactic PLA (Pr = 0.68-0.72), respectively. Good agreement between experimental and theoretical molecular weights of PLA (Mn) and relatively narrow dispersities (Mw/Mn < 1.20) were obtained. Complex 4 showed higher activity for ROP of l- and rac-lactide than 2 or 3, with second-order dependence on monomer concentrations. However, poorly controlled molecular weights and lower heteroselectivity (Pr = 0.61-0.67) were observed. The effect of temperature and catalyst concentration for the ROP of l-lactide using 2 and 3 was also studied.